2019
DOI: 10.1590/1806-3713/e20180355
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of requests for authorization to dispense high-cost medication to COPD patients: the São Paulo “protocol”

Abstract: Objective: A resolution passed by the government of the Brazilian state of São Paulo established a protocol for requesting free COPD medications, including tiotropium bromide, creating regional authorization centers to evaluate and approve such requests, given the high cost of those medications. Our objective was to analyze the requests received by an authorization center that serves cities in the greater metropolitan area of (the city of) São Paulo between 2011 and 2016. Methods: Data regarding the authorizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…7 Based on this protocol, the states of Espírito Santo, Minas Gerais, Ceará, Distrito Federal, Goiás, Maranhão and Pernambuco have also implemented specific protocols regulating the dispensation of tiotropium via the state secretariat. 8 A 2019 survey showed that exacerbation-associated mortality was higher in the 50-60-year-old age group in states without an anticholinergic dispensing protocol. 9 Although long-acting anticholinergics (LAMAs) are widely recommended in the treatment of COPD, until 2012 the only representative available for inhaled use was tiotropium bromide.…”
Section: Rbfhssmentioning
confidence: 99%
“…7 Based on this protocol, the states of Espírito Santo, Minas Gerais, Ceará, Distrito Federal, Goiás, Maranhão and Pernambuco have also implemented specific protocols regulating the dispensation of tiotropium via the state secretariat. 8 A 2019 survey showed that exacerbation-associated mortality was higher in the 50-60-year-old age group in states without an anticholinergic dispensing protocol. 9 Although long-acting anticholinergics (LAMAs) are widely recommended in the treatment of COPD, until 2012 the only representative available for inhaled use was tiotropium bromide.…”
Section: Rbfhssmentioning
confidence: 99%
“…Por ser uma doença crônica, não curável, o tratamento consiste em redução dos sintomas, melhora do estado de saúde e da tolerância ao exercício, redução de riscos e da mortalidade. Faz-se o uso de agentes com ação antioxidante e antiinflamatória, como o N-acetilcisteína, que podem reduzir o estresse oxidativo nas vias aéreas e diminuir as células inflamatórias dos pacientes (Fernandes et al, 2017;Carvalho-Pinto et al, 2019). O N-acetilcisteína apresenta efeitos colaterais comuns como náuseas e diarreia (Fernandes et al, 2017;Carvalho-Pinto et al, 2019).…”
Section: Introductionunclassified
“…In addition, the low availability of spirometry in primary care and the physicians’ lack of knowledge about the local protocol for dispensing medications are factors that can affect the pharmacological treatment of COPD. 10 …”
mentioning
confidence: 99%